2020
DOI: 10.3390/biom10020249
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Telomeric G-Quadruplexes Containing Modified Oligoguanosine Overhangs in Activation of Bacterial Phagocytosis and Leukotriene Synthesis in Human Neutrophils

Abstract: Human neutrophils are the first line of defense against bacterial and viral infections. They eliminate pathogens through phagocytosis, which activate the 5-lipoxygenase (5-LOX) pathway resulting in synthesis of leukotrienes. Using HPLC analysis, flow cytometry, and other biochemical methods, we studied the effect of synthetic oligodeoxyribonucleotides (ODNs) able to fold into G-quadruplex structures on the main functions of neutrophils. Designed ODNs contained four human telomere TTAGGG repeats (G4) including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…We have previously shown [ 2 , 3 ] that synthetic oligonucleotides of various types containing phosphorothioate fragments, to one degree or another, induce the generation of reactive oxygen species by neutrophilic granulocytes. Leukotriene synthesis is regulated by multiple mechanisms, and reactive oxygen species not only provide some peroxide tone required to activate 5-LOX, but through the initiation of NADPH-oxidase-dependent superoxide synthesis, lead to a decrease in NOS activity and protect against NO-induced inhibition of 5-LOX [ 22 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown [ 2 , 3 ] that synthetic oligonucleotides of various types containing phosphorothioate fragments, to one degree or another, induce the generation of reactive oxygen species by neutrophilic granulocytes. Leukotriene synthesis is regulated by multiple mechanisms, and reactive oxygen species not only provide some peroxide tone required to activate 5-LOX, but through the initiation of NADPH-oxidase-dependent superoxide synthesis, lead to a decrease in NOS activity and protect against NO-induced inhibition of 5-LOX [ 22 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…To purify the water/methanol extracts, solid-phase extraction was used on Sep-Pak C18 cartridges (500 mg; Macherey-Nagel, Dueren, Germany), which were conditioned first with methanol, and then with water. Major 5-LOX metabolites were identified by comparing retention times with those of known compounds, as previously described [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…111,112 This event culminates in the development of an innate immune response, which can be applied to limit the spread of pathogens and enhance adaptive immunity, which can be exploited to improve vaccines. 113 Taken together, these considerations make TLR9 one of the most promising targets for fighting against infectious diseases. Chuang et al reported that several synthetic CpG-ODNs generate potent immune stimuli by inducing the production of pro-inflammatory cytokines and a T H 1-dependent immune response.…”
Section: ■ Tlrs and Bacterial Infectionmentioning
confidence: 99%
“…304 Noteworthy, 34, acting via TLR4-MyD88/ TRIF-NF-κB signaling pathway, was able to reduce traumatic brain injury-induced neurons loss, brain edema, and neurobehavioral impairment in rats, subsequently inhibiting neuronal autophagy and neuroinflammation responses in the hippocampus. 305 In inflammation-induced primary microglia, dihydrotestosterone (113) acted as a TLR4 antagonist by limiting LPS-mediated activation, NF-κB, and MAPK p38 signaling pathways and attenuating the release of TNF-α, IL-1β, IL-6, iNOS, COX-2, NO, and PGE2. 306 In another work, the cyanobacteria-derivative TLR4 inhibitor VB3323 was able to decrease microglial activation and morphological alterations of spinal cord neurons.…”
Section: Journal Ofmentioning
confidence: 99%